Perancangan Alat Bantu Pengangkat Pasir dengan Mini Electric Hoist serta Penambahan Sandpot Blasting - Amelia Azzahra Putri; Fipka Bisono; Thina Ardliana (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Sandblasting process at PT. Lintech Duta Pratama had always delays in progress because of the sandpot filling process still using the manual method and the sandpot being used has a small capacity. The author decided to designed a sand lifter using a mini electric hoist to make it easier to fill the sandpot. The sandpot exsting was also redesigned by increasing the capacity, to fulfill blasting productivity per day. This study uses the Ulrich method by creating three design concepts, then will be selected one of the best design according to the selection criteria. Design and analysis of structural strength using Autodesk Fusion 360 software. This study also analyse the ergonomic of the tools by using the RULA method to analyze body posture and risk of injury from these two tools. The strength analysis of the sand lifter structure on the selected design concept obtained a minimum safety factor value is 1.889, a maximum value of von Mises stress is 131.4 MPa at the connection between the rail and the long frame, and a maximum displacement value is 19.2 mm at the foot of the rail. Then the strength analysis of the sandpot structure on the selected design concept obtained a minimum safety factor value is 1.768, a maximum value of von Mises stress is 140.4 MPa at the support sandpot, and a maximum displacement value is 0.84 mm in the shell. The total budget required for the manufacture of this two tools is Rp. 28,763,757,-.